Right Upper Quadrant Pain Following Endoscopic Retrograde Cholangiopancreatography; a Case Report - Nguyen, Lan Thi; Do, Dang Hai; Thai, An Duc; Nguyen, Hoa Thi (Archives of Academic Emergency Medicine, 2022)
Endoscopic retrograde cholangiopancreatography (ERCP) is a standard for diagnosing and treating hepato-pancreatico-biliary (HPB) diseases in clinical settings. ERCP-related complications are relatively common, ranging from 4 to 30%. The most common one is acute pancreatitis. ERCP-related necrotizing pancreatitis accounts for 7.7% of ERCP-related pancreatitis cases. This complication may still be misdiagnosed, which might lead to inappropriate treatment with a worse prognosis. Here, we report a 34-year-old case with ERCP-related necrotizing pancreatitis who was successfully managed, but initially misdiagnosed with biliary peritonitis.